Pengaruh Latihan Lompat Gawang Dan Skipping terhadap Kemampuan Vertical Jump pada Atlet Bolavoli Putra VOPAS Semarang - Ubet, Dicki; Sugiharto (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2024)
A very important component to support the achievement of volleyball athletes in smashing is having explosive leg muscles. By having strong leg muscle explosive power, players will be able to make maximum jumps. This study aims to determine the effect of hurdle hopping and skipping exercises on the vertical jump results of male volleyball athletes in Semarang. The formulation of the problem in this study is 1) Is there any effect of the Hurdle Hopping on the results of the vertical jump? 2) Is there any effect of skipping exercise on the result of vertical jump? The purpose of this study was to determine the increase between goal jumping and skipping in the vertical jump of male vopas volleyball athletes in Semarang. The population in this study amounted to 14 students, using the total sample technique. Hypothesis testing using t-test with the help of the spss for windows version 24 program. The increase in vertical jump results after being given hurdle hopping media reached 9%. The results showed that the skipping exercise media had an effect on increasing the results of the vertical jump in male volleyball athletes in Vopas Semarang. The increase in vertical jump results after being given skipping training media reached 14%.